(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Health attains a major importance in our everyday life. It is necessary to have sound health so as to perform everyday tasks effectively. Good health is the need of human welfare along with the aim of developing a sustained economy. Today, the electronic sensors as used in the medical field are seen to play a vital role in all centers of healthcare. Monitoring E-health of the patient is a crucial advancement in the field of research. Since the prevalence of mankind monitoring the health, the same has emerged to be a concerning issue. Earlier, we saw the existence Ayurveda therapy for medication where medication were extracted directly from herbs and also natural resources with the technique of health monitoring confined to only the nerves inspection by human yet with technological advancement, the technique of medication has turned precise. IoT or Internet of Things is the ecosystem having objects connected physically which are accessible via Internet. These devices of IoT has been used in several fields of application that turn everyday life of users extremely confortable. Such devices have been used for temperature collection, sugar level, and blood pressure, etc., that has been used for evaluation of the patients health condition. The IoT popularity is seen to rise every day in the domain of monitoring remote system. The system of remote monitoring consists of, assets or vehicle, kids or pets monitoring, parking management, fleet management, energy grid management, water and oil leakage etc. Currently Indian hospitals have units of ICU and ICCU units yet because of rising population, facilities given by the hospital isn’t enough, hence we draft a system where the individual’s health can be remotely monitored using IoT in real time.